Radiative screening of fifth forces - Burrage, Clare; Copeland, Edmund J.; Millington, Peter (American Physical Society, 2016)
We describe a symmetron model in which the screening of fifth forces arises at the one-loop level through the Coleman-Weinberg mechanism of spontaneous symmetry breaking. We show that such a theory can avoid current constraints on the existence of fifth forces but still has the potential to give rise to observable deviations from general relativity, which could be seen in cold atom experiments.